Factor Predictors of Prolonged Stress of University Students Taking Online Learning - Dian Pitaloka Priasmoro; Indari Indari; M. Ridwanul Dwiona; Indra Susanto (Journal of Ners and Midwifery, 2022)
The Covid-19 pandemic has caused changes all aspects of people's lives today, especially in the world of education which requires all elements of education to adapt and continue the rest of the semester with online learning. This condition caused prolonged stress, a condition where there is physical, emotional, and mental fatigue caused by excessive. This research was conducted on April 2021 with the aim of identifying predictors of prolonged stress of students taking online learning. The method used descriptive approach. The data analysis used factor analysis with KMO and Bartlett's Test methods. The population in this research were all students of nursing study program ITSK RS dr. Soepraoen Malang total 815. The sampling technique used accidental sampling with total sample of 279. The instrument used Maslach Burnout Inventory which distributed online by google forms. The results showed that almost all of the students who experienced mild to moderate prolonged stress were regular students with a total of 252 people (90.3%), low to moderate respondents were unmarried, organizational factors causing prolonged stress were institutional support, more than half of the respondents, 27 people (9,7 %) who felt adequate support from the institution experienced prolonged stress in the mild to moderate category. The dominant factor was student's status as a regular student or assignment or study permit with the significance value was 0.001 <0.05. It is recommended that students actively seek support systems from family and friends as well as educational institutions that are consistent in supporting students